If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x-9=6x-31
We move all terms to the left:
2x-9-(6x-31)=0
We get rid of parentheses
2x-6x+31-9=0
We add all the numbers together, and all the variables
-4x+22=0
We move all terms containing x to the left, all other terms to the right
-4x=-22
x=-22/-4
x=5+1/2
| 2(x+5.00)=34.00 | | 4(b+3)=-28 | | 15-4(x=3)=19 | | 13x+5x+19=19x+10 | | 9a-3=12-5a | | 11+x-8=2x-10 | | 5x+16➗2=x+5 | | x+18+4x-7=4x+15 | | 5b+7=4(b-6) | | 6x-16+3x+12=8x+15 | | 7+x-8=2x-12 | | 7a+5=8(a+2) | | -5p+37=12 | | 6x-7=8x-17 | | 8(c+5)=6c+2 | | 21q+4=7q-5 | | 0.65x=10 | | 7.4=-t/46 | | 3x+1=-7x-99 | | 65x=10 | | 4j+3=18 | | 4-6t=-5t | | 5^(x-2)=6(2x+1) | | 7x8=84 | | 12=+20x=132 | | x-39=2(180-x) | | X2+7x+12=9 | | 3^4x+3=15 | | 8x2+40x-122=0 | | 8x2+40x-112=0 | | 1/3(x-3)=4/3x+5 | | 5r+3=13 |